Заповедник убийц: повести / Николай Крамной - Крамной Николай Николаевич (Черная кошка, 1995)
Экземпляры: аб. ЦБ (2018.03.05) / Инвентарный номер: 4309 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: К78 / ББК: 84(2Рос=Рус)6